Urdu Drama of Pakistan Television: A Critical Analysis - Saher Mubeen; Dr. Mohammad Afzal But (Zaban-o-Adab, 2023)
Drama is the biggest source of entertainment. PTV drama was the golden era for Urdu drama. As those dramas were the true representation of Pakistani culture and social issues. Those dramas still have a powerful impact and messages. They still have a special place in Pakistani dramas history. Thus all the genres of literature are the mirror and reflection of their culture and society .But when it becomes to present the culture practically, drama is the most powerful source of it. The name of PTV will be written in golden letters in the beginning of Urdu TV drama. Because the way PTV had beautifully presented Pakistani culture in its dramas no other TV channel could do it ever. PTV was the golden era for dramas. Its dramas have always come with moral lessons for its viewer.